NEWLY DEVELOPED BLOOD PUMP AND CONTROL UNIT FOR NEONATAL EXTRACORPOREAL MEMBRANE OXYGENATION - ITO, F.; UMEDA, T.; SEO, T.; TAKAGI, H.; SUZUKI, A.; ITO, T. (Jinko Zoki, 1994)
We developed a new automatically driven blood pump for neonatal extracorporeal membrane oxygenation circuit. Our blood pumps consisted of a pair of sac-typed air driven blood pumps with LED sensors, which are controlled with three types of pumping mode. A-mode: the output was as same as the intake meeting the Starling's law, B-mode: the output was modified by delaying compression of the blood chambers after they filled, and C-mode: the blood pumps kept a constant output by applying positive or negative pressure on the air chambers regardless of the resistence at both the inflow and outflow. These characteristics of each mode were demonstrated on a mock circulation. Our experiment suggests the usefulness combining these modes for neonatal ECMO, and makes all of ECMO course automatically controlled and safely operated starting and maintaining with A-mode and B-mode, and weaning performed with C-mode.